2017
DOI: 10.1007/s11606-017-3988-z
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Detection of Delayed Test Result Follow-Up in Patients with Hypothyroidism

Abstract: BACKGROUND: Delays in following up abnormal test results are a common problem in outpatient settings. Surveillance systems that use trigger tools to identify delayed follow-up can help reduce missed opportunities in care. OBJECTIVE: To develop and test an electronic health record (EHR)-based trigger algorithm to identify instances of delayed follow-up of abnormal thyroid-stimulating hormone (TSH) results in patients being treated for hypothyroidism. DESIGN: We developed an algorithm using structured EHR data t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, we combined conventional (telephone follow-up) and electronic surveillance methods to ensure timeliness and a higher participation rate. Although electronic monitoring is widely used, there are obstacles to its use in real-world applications [ 38 ], such as potential delays [ 39 ] and low response rates; thus traditional manual follow-up still plays an important role in management. The key to resolving these limitations is to consider how to change the passive follow-up pattern to one in which patients actively report symptoms, which means patients actively report to the electronic monitoring system when menstruating.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we combined conventional (telephone follow-up) and electronic surveillance methods to ensure timeliness and a higher participation rate. Although electronic monitoring is widely used, there are obstacles to its use in real-world applications [ 38 ], such as potential delays [ 39 ] and low response rates; thus traditional manual follow-up still plays an important role in management. The key to resolving these limitations is to consider how to change the passive follow-up pattern to one in which patients actively report symptoms, which means patients actively report to the electronic monitoring system when menstruating.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, e-triggers have recently shown effectiveness in proactively detecting delays in care after an abnormal test result suspicious for cancer, [18][19][20]22,[80][81][82] kidney failure, 83,84 infection, 83 and thyroid dysfunction. 85 Similar, more prospective approaches could be applied to reduce diagnostic error risk for patients presenting to the ED. There are several limitations of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Certain e-trigger tools can additionally monitor for high-risk situations prospectively, such as when risk of harm is high, even if no harm has yet occurred. Several studies have shown that e-trigger tools offer promise in detecting errors of omission, such as detecting delays in care after an abnormal test result suspicious for cancer,26–30 35 kidney failure,29 36 infection29 and thyroid conditions,37 as well as patients at risk of delayed action on pregnancy complications 38 39. Such triggers can identify situations where earlier intervention can potentially improve patient outcomes.…”
Section: Conceptualising Diagnostic Safety E-triggersmentioning
confidence: 99%